Empirical Study of Deep Learning-based Technology for Place Image Collecting - Jin-wook Jang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research study designed a location image collecting technology. It provides the exact location information of an image which is not given in the photo to the user. Deep learning technology analysis and collects the images. The purpose of this service system is to provide the exact place name, location and the various information of the place such as nearby recommended attractions when the user upload the image photo to the service system. Suggested system has a deep learning model that has a size of 25.3MB, and the model repeats the learning process 50 times with a total of 15,266 data, performing 93.75% of the final accuracy. In a performance test, the final accuracy of the model is calculated 93.75%. This system can also be linked with various services potentially for further development.